State and non-state regulation in African protracted crises: governance without government? - Raeymaekers, Timothy; Menkhaus, Ken; Vlassenroot, Koen (Afrika Focus, 2008)
This article introduces a collection of papers that treat the question of governance in conditions of protracted crises in Subsahara Africa. Contrary to the widespread belief that African conflicts are little more than (undoubtedly complex and intractable) instances of anarchy and chaos, the authors present the reader with tangible evidence of the existence of non-state governance processes by constituencies attempting to manage the perils of long periods of violent strife and state failure. Their aim is to move beyond the purely empirical and to theorize and situate such phenomena of non-state governance in the broader context of political and social change that is currently reshaping Africa. Key words: protracted crisis, non-state governance, political order